Room temperature synthesis of two-dimensional multilayer magnets based on α-CoII layered hydroxides - Oestreicher, Víctor (2022)
Research on two-dimensional (2D) materials is one of the most active fields in materials science and nanotechnology. Among the members of the 2D family, layered hydroxides (LHs) represent an exceptional case of study due to their unparalleled chemical versatility which allows the modulation of their physicochemical properties at will. Nowadays, LHs based on earth-abundant metals are key materials in the areas of energy storage and conversion, hybrid materials or magnetism. ɑ-Co hydroxides (Simonkolleite-like structures) are promising phases with tuneable electronic and magnetic properties by ligand modification. However, even in the simple case of ɑ-CoII hydroxychlorides, the preparation of well-defined large 2D crystals is not straightforward, hindering the development of fundamental studies. Herein, we present the synthesis of 2D hexagonal crystals with outstanding size-thickness relationship (diameter > 5 μm and thickness of 20 ± 7 nm) by a simple homogeneous synthesis taking place at room temperature. In structural terms, no differences are observed between our layered materials and those obtained hydrothermally. However, dynamic susceptibility measurements alert about different arrangements of the magnetic sublattices, which have been rationalized with structural DFT calculations. This work provides an extremely easy bottom-up method to obtain high-quality 2D crystals based on ɑ-CoII hydroxides, paving the way for the development of fundamental studies and applications.